Stories for eight-year-olds - Cooling, Wendy (Penguin Books Ltd; UK, 1996)
"Stories for Eight-Year-Olds" is a collection of engaging and imaginative tales designed to entertain and inspire young readers, fostering creativity and moral lessons.